ENTREPRENEURSHIP AS THE MOST IMPORTANT DRIVER OF EMPLOYMENT - Temirqulov Alisher Abduraimovich (Modern American Journals, 2025)
This paper examines the role of entrepreneurship in job creation. The business development in Uzbekistan and its impact on the labor market are analyzed. The author explores the economic, social and organizational factors influencing the development of entrepreneurship. The theoretical and practical aspects of the impact of small and medium-sized businesses on the labor market, regional development, and the introduction of new technologies and innovations are considered. The article suggests practical measures such as changing the education system, stimulating digital and innovative ideas, creating a favorable organizational environment to support entrepreneurship and increase employment in the country's economy. The study provides important information about the relationship between entrepreneurship and employment, as well as ways to ensure sustainable economic growth in Uzbekistan and stability in the labor market.
Keywords: Entrepreneurship, employment, job creation, small and medium-sized businesses, innovation, labor market, institutional environment, digital economy, sustainable development.